The nonsense factory : the making and breaking of the American legal system - Gibney, Bruce Cannon (Hachette Books, 2019)
Our trial courts conduct hardly any trials, our correctional systems do not correct, and the rise of mandated arbitration has ushered in a shadowy system of privatized "justice." Meanwhile, our legislators can't even follow their own rules for making rules, while the rule of law mutates into a perpetual state of emergency. The legal system is becoming an incomprehensible farce. How did this happen? In The Nonsense Factory, Bruce Cannon Gibney shows that over the past seventy years, the legal system has dangerously confused quantity with quality and might with legitimacy. As the law bloats into chaos, it staggers on only by excusing itself from the very commands it insists that we obey, leaving Americans at the mercy of arbitrary power. By examining the system as a whole, Gibney shows that the tragedies often portrayed as isolated mistakes or the work of bad actors-police misconduct, prosecutorial overreach, and the outrages of imperial presidencies-are really the inevitable consequences of law's descent into lawlessness.